HAYVONLARNING XILMA- XILLIGI MAZVUSINI OQITISHDA MULTIMEDIA, 3D FORMAT MODELLARI VA VIRTUAL LOBARATORIYA ASOSIDA OQITISH METODIKASI (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This chapter proposes and analyzes a methodology for teaching animal diversity by integrating modern pedagogical technologies, specifically multimedia, 3D format models, and virtual laboratories. Against the backdrop of limitations in traditional teaching methods and challenges in student engagement and deep understanding of the subject, the implementation of these technologies in the educational process is substantiated to enhance student motivation, visualize complex concepts, develop practical skills, and expand opportunities for ethical compliance. The chapter thoroughly discusses the theoretical foundations, practical advantages, expected outcomes, key aspects of implementation, and future research directions related to these technologies.